Prevalence of abnormal uterine bleeding according to new International Federation of Gynecology and Obstetrics classification in Chinese women of reproductive age: A cross-sectional study - Sun, Yu (Medicine (Baltimore), 2018)
The PALM-COEIN classification for causes of abnormal uterine bleeding (AUB) was proposed by the International Federation of Gynecology and Obstetrics (FIGO) in 2011, which has been gradually applied in the diagnosis of AUB in the past 2 years in China. However, there are no reports yet on the causes of chronic AUB among Chinese women with this new classification system. The purpose of this study was to describe the prevalence of the causes of chronic AUB among Chinese women of reproductive age using the PALM-COIEN classification system. This is a cross-sectional study. Beijing Shijitan Hospital, Capital Medical University. A total of 1053 women aged 15 to 55 years with chronic AUB were evaluated between November 2016 and May 2017. Prevalence of the causes of chronic AUB using the PALM-COEIN classification. AUB-O was the most frequent finding in women with chronic AUB, accounting for 608 (57.7%) cases. AUB-P was found in 171 (16.2%) women, AUB-L in 130 (12%) women, AUB-A in 52 (4.94%) women, AUB-E in 28 (2%) women, AUB-I in 23 (2%) women, AUB-M in 20 (1.9%) women, AUB-C in 10 (1%) women, and AUB-N in 10 (0.9%) women. Ovulatory dysfunction (AUB-O) is the most common cause of AUB among the nonstructural causes. Endometrial polyps (AUB-P) are the most common among the structural causes, followed by uterine fibroids (AUB-L) and uterine adenomyosis (AUB-A).